Not My Fault to Phub Friends! Individual, Social, and Technological Influences on Phubbing and Its Consequences - Juhyung Sun; Doyle Yoon (Human Behavior and Emerging Technologies)
Fphubbing (friend phubbing) indicates snubbing friends by checking and/or using one’s smartphone. This study examined three approaches to provide more detailed insights and comprehensive views of phubbing: individual differences, social influences, and technological influences on Fphubbing. In addition, this study explored the outcomes of Fphubbing and further examined the mediating role of Fphubbing between proposed predictors and consequences in this study. A sample of 266 college students (aged between 18 and 38, Mage=20.02) also revealed that (a) smartphone dependence was positively associated with Fphubbing, while self-control had a negative association with Fphubbing; (b) social norms were positively related to Fphubbing; and (c) technology overload and interruptive notifications were positively associated with Fphubbing. We also found that Fphubbing was negatively associated with friendship commitment and satisfaction, respectively. Further, Fphubbing served as a mediator in the proposed model.